Radical Cystectomy vs. Radiotherapy in Urothelial Bladder Cancer in Elderly and Very Elderly Patients - Horlemann, Benedikt; Würnschimmel, Christoph; Hoeh, Benedikt; Sorce, Gabriele; Chierigo, Francesco; Flammia, Rocco Simone; Tian, Zhe; Saad, Fred; Briganti, Alberto; Shariat, Sharokh F; Galucci, Michele; Chun, Felix K H; et al. (Clinical genitourinary cancer, 2022)
INTRODUCTION: Controversy regarding cancer-specific mortality (CSM) of elderly and very elderly patients with muscle-invasive, non-metastatic, urothelial carcinoma of the urinary bladder (UCUB) undergoing radical cystectomy (RC) vs radiotherapy (RT) still exists. MATERIALS AND METHODS: In the 2004-2016 Surveillance, Epidemiology and End Results (SEER) database, we identified 2663 UCUB patients aged 75-79 (1808 RC vs 855 RT) and 3569 UCUB patients aged 80-89 (1551 RC vs 2018 RT). After stratification for concomitant chemotherapy, propensity score matching (PSM) between RC and RT was applied and competing-risks regression models addressed CSM and OCM. RESULTS: In the cohort aged 75-79, five-year CSM rates were 22.0 vs 49.0% for RC only vs RT only and yielded a HR of 0.41 (95% confidence interval (CI) 0.30-0.57, p<0.001) favoring RC only. Five-year CSM rates were 28.3 vs 44.3% for RC with chemotherapy vs trimodal therapy (TMT) and yielded a HR of 0.48 (95% CI 0.35-0.65, p<0.001) favoring RC with chemotherapy. In the cohort aged 80-89, five-year CSM rates were 24.2 vs 48.9% for RC only vs RT only and yielded a HR of 0.42 (95% CI 0.33-0.52, p<0.001) favoring RC only. Five-year CSM rates were 19.6 vs 43.2% for RC with chemotherapy vs TMT and yielded a HR of 0.43 (95% CI 0.28-0.67, p<0.001) favoring RC with chemotherapy. CONCLUSIONS: In elderly and very elderly patients, radical cystectomy is associated with virtually half the CSM rate than radiotherapy, regardless of concomitant chemotherapy administration.
Keywords: senioři; nádory močového měchýře; program SEER; chemoradiation; survival; karcinom z přechodných buněk; mužské pohlaví; surgery; Urinary Bladder; Cystectomy; trimodal therapy; močový měchýř; SEER Program; ženské pohlaví; Humans; radiation; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; Female; Aged; lidé; Male; cystektomie